Highly Thermostable Xylanase Production from A Thermophilic Geobacillus sp. Strain WSUCF1 Utilizing Lignocellulosic Biomass - Bhalla, Aditya; Bischoff, Kenneth M.; Sani, Rajesh Kumar (Frontiers in Bioengineering and Biotechnology, 2015)
Abstract Efficient enzymatic hydrolysis of lignocellulose to fermentable sugars requires a complete repertoire of biomass deconstruction enzymes. Hemicellulases play an important role in hydrolyzing hemicellulose component of lignocellulose to xylo-oligosaccharides and xylose. Thermostable xylanases have been a focus of attention as industrially important enzymes due to their long shelf life at high temperatures. Geobacillus sp. strain WSUCF1 produced thermostable xylanase activity (crude xylanase cocktail) when grown on xylan or various inexpensive untreated and pretreated lignocellulosic biomasses such as prairie cord grass and corn stover. The optimum pH and temperature for the crude xylanase cocktail were 6.5 and 70ºC, respectively. The WSUCF1 crude xylanase was found to be highly thermostable with half-lives of 18 and 12 days at 60 and 70ºC, respectively. At 70ºC, rates of xylan hydrolysis were also found to be better with the WSUCF1 secretome than those with commercial enzymes, i.e., for WSUCF1 crude xylanase, CellicHTec2, and AccelleraseXY, the percent xylan conversions were 68.9, 49.4, and 28.92, respectively. To the best of our knowledge, WSUCF1 crude xylanase cocktail is among the most thermostable xylanases produced by thermophilic Geobacillus spp. and other thermophilic microbes (optimum growth temperature ≤70ºC). High thermostability, activity over wide range of temperatures, and better xylan hydrolysis than commercial enzymes make WSUCF1 crude xylanase suitable for thermophilic lignocellulose bioconversion processes.